Pela- Gandong and Harmonization Life of Brotherhood (Orang Basaudara) (Study Case The Relations of Islam and Christianity Post Conflict in Ambon) - M. Attamimy (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
In post conflict period, Moluccas people were re-echoed the desire to be a civilized society and a dignified. Moluccas Community believes that the spirit of Pela-Gandong is able to glue back the kinship that had marred. Pela is cultural friendships which have been institutionalized in every heart, mind, and behavior of the Moluccans, itâ€™s mean that they come from the same culture, although their religion is different. Pela-Gandong is a â€œmental awareness â€œof the â€œorang Basudaraâ€ were so strong, so whatever the burden and responsibility of the â€œorang Basudaraâ€ is a shared of responsibility. This Relationship has relevance to the teaching of religion in ukhuwwah concept. Therefore, the embodiment of teaching of Pela and the values which contained itâ€™s none other the practice of religion. Instead, the reluctance to hold of Pela tradition, itâ€™s same as reluctant to implement the values of religion itself.